Enha Water: Air Mineral Kemasan sebagai Upaya Pemberdayaan Ekonomi Berbasis Pesantren di Bengkalis, Riau - Muhammad Ashsubli (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study examines Enha Water, a bottled mineral water business developed as an economic empowerment strategy based on Islamic boarding schools (pesantren) in Bengkalis Regency, Riau Province. The background of this research stems from the importance of the economic independence of Islamic boarding schools (pesantren) as Islamic educational institutions that play a role not only in religious development but also in strengthening the community's economy. The research method used was a qualitative case study approach. Data collection was conducted through in-depth interviews, observation, and documentation with the boarding school administrators, students, and related parties involved in the Enha Water business management. The results indicate that Enha Water's existence has significantly contributed to increasing the boarding school's income, creating jobs for students and the surrounding community, and fostering an entrepreneurial spirit based on Islamic values. Furthermore, this business also serves as a practical learning tool for students in economics and business management. Challenges faced include limited capital, marketing distribution, and competition with similar products. This study concludes that Enha Water has the potential to become a model for sustainable Islamic boarding school economic empowerment if supported by professional management, product innovation, and synergy with various stakeholders.